DEVELOPMENT OF METHODOLOGICAL APPROACHES AND TOOLS FOR THE MANAGEMENT OF MEDICAL WASTE USING INTERNET OF THINGS TECHNOLOGIES - Abduvalova, А.Д.; Akhmetzhanova, Ш.Е.; Oralbekova, Ж.О.; Eshmakhanova, Т.К.; Shymyrbek, А. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article discusses the issues of developing methodological foundations and mechanisms for collecting, structuring and analyzing data for medical waste management. This article discusses the use of Internet of Things (IoT) technologies to optimize the collection, transportation, and disposal of medical waste. Methods of modeling business processes using intelligent sensors are proposed. The methods of designing databases that ensure reliable storage, systematization and analysis of information on the types, volumes and routes of movement of medical waste are described. The developed model makes it possible to increase the efficiency of waste management, minimize environmental risks and reduce logistics costs. The authors offer recommendations for improving waste management based on digital technologies. The proposed solutions are aimed at improving environmental safety, reducing health risks and optimizing resources in the healthcare sector.